Mukrim MN Enterprise / Mazliani Mohd Muslim, Nurulfazila Gala … [et al.] - MOHD MUSLIM, MAZLIANI; GALA, NURULFAZILA; NOORZAMBRE, NURULSHUHADA; ABD HADI, FATIN SYAFIKAH; SHAARI, NORSHUHADA (2019)
Mukrim MN Enterprise is a start-up soya drink and Tau Fu Fa retail establishment located in Segamat, Johor. Mukrim MN Enterprise expects to catch the interest of a regular loyal customer base with its broad variety of soy products. The company plans to build a strong market position in the town, due to the partners' industry experience and a mild competitive climate in the area.Mukrim MN Enterprise aims to offer its products at a competitive price to meet the demand of the middle-to higher-income local market area residents and tourists.